Aphasia and its therapy - Basso, Anna (Oxford University Press, 2003)
This is the first single-authored book to attempt to bridge the gap between aphasia research and the rehabilitation of patients with this language disorder. Studies of the deficits underlying aphasia and the practice of aphasia rehabilitation have often diverged, and the relationship between theory and practice in aphasiology is loose. The goal of this book is to help close this gap by making explicit the relationship between what is to be rehabilitated and how to rehabilitate it. Early chapters cover the history of aphasia and its therapy from Broca's discoveries to the 1970's, and provide a.